Pentingnya Literasi Keuangan Dalam Pengambilan Keputusan Investasi Bagi Generasi Milenial - Achmad Fadjar; Andry Arifian Rachman; Syafrizal Ikram (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Not a few losses that occur due to errors in the selection of assets or investment projects by a company or individual with the original intention of obtaining profitable results in the future but in reality experiencing losses due to a lack of understanding of financial literacy. The sample in this study used millennial generation S2 Accounting students at Widyatama University graduate school as respondents. Data obtained through questionnaires and interviews with data analysis using simple linear regression. The results showed that there was an influence of financial literacy on investment decision making for the millennial generation. Based on the results of descriptive analysis, it is known that in making investment decisions it is less supported by mastery of technical analysis in making investment decisions, one of the factors causing this is because financial literacy lacks understanding of financial management including basic concepts and financial products. Keywords: Financial Literacy, Investment Decision Making, Millennial Generation